Analysis of the Effect of Population, Open Unemployment Rate, and Economic Growth on Poverty Rates in Lamongan Regency - Azmy, Nurul; Setiawati, Ririt Iriani Sri (PT. Riset Press International, 2025)
The poverty rate in Kabupaten Lamongan in 2022 is still high, above the average poverty rate in East Java. Poverty levels can certainly be an obstacle to development, and several factors cause high poverty rates in Lamongan Regency, namely population, open unemployment rates, and economic growth. This study aims to analyze the independent variables, including population, open unemployment rate, and economic growth, that affect the poverty rate in Lamongan Regency. This research uses quantitative methods with time series data over 15 years, from 2008 to 2022. The technique used is multiple linear regression. The results show that the population and open unemployment rate variables affect the poverty rate in Lamongan Regency. In contrast, the economic growth variable has no effect on the poverty rate in Lamongan Regency.